2013
DOI: 10.1007/s40415-013-0037-y
|View full text |Cite
|
Sign up to set email alerts
|

Thismia singeri (Thismiaceae), an augmented description and first record for Brazil

Abstract: Thismia singeri, is described for the first time for Brazil, being the first record of this family for Para Śtate and the third record for this rare species in nature. In Para ´state, northern Brazil, this species was found growing in Itaituba municipality near the River Tapajo ´s, in a well preserved submontane rain forest with a dense canopy. Due to the holotype is incomplete, we provide a more comprehensive description for this species based on complete individuals, thus clarifying some aspects of its morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…Therefore, there is a gap of occurrence of Thismiaceae between the Amazonia and the Atlantic Rainforest, which is covered by the Brazilian Cerrado. Because of its rare occurrence and very small habit, some authors have made new descriptions of this genus and new distributions in recent years (e.g., Dančák et al 2013;Voloschen et al 2013;Truong et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a gap of occurrence of Thismiaceae between the Amazonia and the Atlantic Rainforest, which is covered by the Brazilian Cerrado. Because of its rare occurrence and very small habit, some authors have made new descriptions of this genus and new distributions in recent years (e.g., Dančák et al 2013;Voloschen et al 2013;Truong et al 2014).…”
mentioning
confidence: 99%
“…With the assistance of the literature (Maas et al 1986;Mancinelli et al 2012;Voloschen et al 2013), we have identified the species as Thismia panamensis (Standl.) Jonker (Figure 2).…”
mentioning
confidence: 99%
“…Nevertheless, these observations deserve further evaluation, as our data were obtained with drops 1.2 m from the ground, whereas for drops that fall from higher elevations, such as the canopy at >30 m, the dispersion distance can increase significantly. Similar data, even without the evaluation of spatial distribution, suggest that Thismia populations are always clumped (Chantanaorrapint 2012; Li & Bi 2013; Voloschen et al 2013; Mar & Saunders 2015; Suetsugu et al 2018), which may be related to more humid parts of the habitat, specific interactions, or even some specific dispersal mechanism (Gomes et al 2019).…”
Section: Discussionmentioning
confidence: 87%
“…clavigera , suggesting that seed dispersal occurred by rain splash. Cup‐shaped, dehiscent fruits are a common characteristic conserved in this group, being reported for several species of the genus (Jarvie 1996; Chantanaorrapint 2008; Voloschen et al 2013; Mar & Saunders 2015; Suetsugu et al 2018; Silva et al 2020). A unilocular ovary, with a straight and smooth inner epidermis, as well as exposure of seeds to a mucilaginous matrix inside the fruits, as observed in T .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation